The impact of corporate social responsibility on brand attitude and purchase intention of Vietnamese generation Z consumers: A PLS-SEM approach - Nguyen, Minh Vu (Journal of Finance - Marketing Research, 2025)
Corporate Social Responsibility (CSR) has become a crucial strategy for brands to align with ethical consumer expectations, particularly among Generation Z. This study investigates how perceived CSR influences brand attitude and purchase intention among Vietnamese Generation Z consumers, adopting the Hierarchy of Effects (HOE) model. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), data from 312 respondents were analyzed to test six hypotheses. Results reveal that perceived CSR does not directly affect purchase intention but exerts a significant indirect impact through brand attitude. Furthermore, Generation Z's pre-existing CSR attitudes increase the association between perceived CSR and brand attitude, as well as brand attitude and purchase intention. The findings underline brand attitude as a key mediator and highlight Gen Z’s role as a moderating force in consumer behaviour motivated by CSR. This research extends the HOE model to CSR contexts, offering theoretical insights into the psychological mechanisms linking CSR to purchase decisions. Practically, it advises brands to prioritize authentic CSR communication and align initiatives with Gen Z’s values to foster long-term loyalty in emerging markets like Vietnam.